Análisis financiero al Conservatorio Superior de Música Jaime Mola, de la ciudad de Quito, periodo 2021- 2022 - Valdez Huanca, Dolores Enith (2024)
This article of financial analysis is of great importance to obtain reliable results on the financial reality of an institution. Becoming a topic with great breadth to investigate; to determine what is the reality of the institutions regarding to their economic situation. The purpose of this study is to analyze the financial situation of “Jaime Mola” Conservatory of Music during the years 2021 - 2022, through the analysis of its financial statements. Horizontal and vertical analysis techniques and the calculation of key financial indicators were used to evaluate the evolution of the institution and detect possible areas for improvement. The results obtained refer to the year 2022, from the vertical analysis revealed an 86% increase in current assets, while non- current or demandable assets, which are those that will be liquidated in a period of more than one year, decreased by 79%. A decrease in current liabilities of 20%, and an increase in equity of 80%. The horizontal analysis made it possible to identify the percentage composition of each item within the financial statements, showing a decrease in income of 28%, and an increase in operating expenses of -17% with a value of $133,052.15. The calculation of financial indicators such as liquidity and solvency, allowed evaluating the capacity of the Conservatory to comply with its short-term obligations, with a current ratio of 3.9 and in the acid test of 2.7, indicating its capacity to generate profits, and the efficiency in the use of its resources. The results obtained show that it is in a good financial situation. The institution indicates a relatively low level of indebtedness and a relatively low level of leverage. As a conclusion, the financial analysis performed reveals that “Jaime Mola” Conservatory of Music faces challenges in terms of strengthening its assets, increasing revenues, minimizing costs, optimizing revenue, minimizing costs, and optimizing resources. The following actions are recommended to improve the financial situation of the institution: carry out a detailed analysis of costs, explore new sources of funding income, invest in technology by offering online educational programs. This study contributes to a better understanding of the conservatory's financial situation and provides a solid basis for making strategic decisions to ensure the sustainability of the institution in a long term.